In-hospital outcomes of transcatheter aortic valve replacement in patients with chronic and end-stage renal disease: a nationwide database study - Marta Lorente-Ros; Subrat Das; Aaqib Malik; Francisco Jose Romeo; Jose S. Aguilar-Gallardo; Maya Fakhoury; Amisha Patel (BMC Cardiovascular Disorders, 2024)
Abstract Background Chronic kidney disease (CKD) and end-stage renal disease (ESRD) have been associated with worse outcomes after transcatheter aortic valve replacement (TAVR). With TAVR indications extending to a wider range of patient populations, it is important to understand the current implications of chronic renal insufficiency on clinical outcomes. We aim to determine the impact of CKD and ESRD on in-hospital outcomes after TAVR. Methods We queried the National Inpatient Sample for TAVR performed between 2016 and 2020 using International Classification of Diseases-10th Revision codes. We compared in-hospital mortality and clinical outcomes between three groups: normal renal function, CKD and ESRD. The association between CKD/ESRD and outcomes was tested with multivariable logistic regression analyses, using normal renal function as baseline. Results In the five-year study period, 279,195 patients underwent TAVR (mean age 78.9 ± 8.5 years, 44.4% female). Of all patients, 67.1% had normal renal function, 29.2% had CKD, and 3.7% had ESRD. There were significant differences in age, sex, and prevalence of comorbidities across groups. In-hospital mortality was 1.3%. Compared to patients with normal renal function, patients with renal insufficiency had higher in-hospital mortality, with the highest risk found in patients with ESRD (adjusted odds ratio: 1.4 [95% confidence interval: 1.2–1.7] for CKD; adjusted odds ratio: 2.4 [95% confidence interval: 1.8–3.3] for ESRD). Patients with CKD or ESRD had a higher risk of cardiogenic shock, need for mechanical circulatory support, and vascular access complications, compared to those with normal renal function. In addition, patients with ESRD had a higher risk of cardiac arrest and periprocedural acute myocardial infarction. The incidence of conversion to open heart surgery was 0.3% and did not differ between groups. Post-procedural infectious and respiratory complications were more common among patients with CKD or ESRD. Conclusion Patients with CKD and ESRD are at higher risk of in-hospital mortality, cardiovascular, and non-cardiovascular complications after TAVR. The risk of complications is highest in patients with ESRD and does not result in more frequent conversion to open heart surgery. These results emphasize the importance of individualized patient selection for TAVR and procedural planning among patients with chronic renal insufficiency.